Francis Scott Fitzgerald, between pedagogical puritanism and postmodern morality - Raquel CERCÓS I RAICHS; Conrad VILANOU TORRANO (Historia de la Educación, 2019)
This article reviews what the experience of the First World War (1914-1918) meant for the American generation that promoted what Francis Scott Fitzgerald (1896-1940) called «Jazz Age», period corresponding to the decade of the twenties until the crack of 1929. It attends the novels of this American writer to trace the emergence of a new moral that eroded the pedagogical puritanism of the time of the pioneers. This change brought a new educational horizon away from the ideal of the Christian student that had represented university institutions such as Princeton, whose classrooms passed our protagonist before joining the army. It is a pedagogical chronicle of a literary generation that, after visiting Europe in the 1920s, broke with the tradition of the biblical story, with which it anticipated postmodern morality.